(untitled) - Saladin, Kenneth S. (New York, NY, 2018)
This book weaves together science, clinical applications, history and evolution of the body with vibrant photos and art to convey the beauty and excitement of the subject.
Keywords: Sinh lý học người,Giải phẫu người,Human physiology,Human anatomy; Sách giáo khoa,Sách giáo khoa,Textbooks,Textbooks